Integrated law enforcement in crminal action of legislative general in makassar city - Arbiansyah Haseng Malapua (Indonesia Prime, 2020)
Integrated Law Enforcement in criminal Action of Legislative General Election in Makassar City. The research aimed to investigate the law enforcement in following up the criminal action of the legislative general election, the factors influencing the effectiveness of the law enforcement of the criminal action of the legislative general election carried out by the law enforcement apparatus in Makassar City. The research was conducted in the General Election Supervising Board of South Sulawesi Province, Makassar City Resort Police, Office of the Counsel for the Prosecution of Makassar, District Court of Makassar City. Data were collected by an interview and documents related to the problems examined. The research result indicates that the law enforcement authority in handling the legal matters in the legislative general election, has been carried out in line with he mandate of the acts. However, the factors such as: the substance, structure, human resources, facilities, infrastructures and culture mostly influence the course of the law enforcement. Besides, there is also the dominant factor namely the evidence determination which is imposed on the general election supervisors, very short handling time, lack of community’s participation in supervising the legislative general election, so that the law enforcement in the legislative general election carried out by the law enforcement apparatus is less maximal.